“We Are All Potential Migrants”: Insecurity, Forced Displacement, and the Remaking of Rural Livelihoods in Northwestern Nigeria, 2018–2025 - Felix Tabi Okorn (Universitas Negeri Makassar, 2026)
The escalation of armed banditry in northwestern Nigeria since 2018 has generated one of the country’s most severe displacement crises, forcing over 300,000 people from their rural communities across Zamfara, Katsina, Kaduna, Niger, and Sokoto States. While existing scholarship has focused on the immediate humanitarian dimensions of this crisis and on the military and policy responses of the state, considerably less attention has been paid to the long-term reconfiguration of rural livelihoods among displaced populations. This article examines how forced migration induced by banditry has reshaped agricultural practices, labour markets, and land tenure systems in both source communities and host areas. Drawing on a political economy framework and the concept of forced immobility, the study employs a mixed-methods design combining a household survey of 300 displaced and host-community households across three local government areas in Zamfara and Katsina States with in-depth interviews with community leaders, agricultural extension workers, and local government officials. Findings reveal that displacement has precipitated a fundamental restructuring of agrarian livelihoods characterised by the collapse of household food production, the transformation of land access from customary to monetised arrangements, the erosion of communal labour systems, and the emergence of new patterns of dependency on humanitarian assistance and urban informal economies. The study further demonstrates that displacement does not affect all households uniformly. Differential access to social networks, financial capital, and off-farm skills produces divergent livelihood trajectories, with some households achieving partial recovery while others descend into chronic vulnerability. The paper concludes that displacement is not merely a temporary disruption but a process of profound economic restructuring with lasting implications for food security, rural governance, and the political economy of the region.